Intravoxel incoherent motion diffusion‐weighted MR imaging of breast cancer at 3.0 tesla: Comparison of different curve‐fitting methods. Issue 2 (19th November 2014) - Suo, Shiteng; Lin, Naier; Wang, He; Zhang, Liangbin; Wang, Rui; Zhang, Su; Hua, Jia; Xu, Jianrong
<x xml:space="preserve">Abstract</x> Background To compare three different curve‐fitting methods for intravoxel incoherent motion (IVIM) analysis in breast cancer. Methods Diffusion‐weighted imaging was acquired in 30 patients with breast cancer using seven b‐values (0–800 s/mm2). Three curve‐fitting methods were used for biexponential IVIM analysis: a. Direct estimation of D (diffusion coefficient), D* (pseudodiffusion coefficient) and f (perfusion fraction) (Method 1), b. Estimation of D first and then D* and f (Method 2), c. Estimation of D and f first and then D* (Method 3). Goodness‐of‐fit, parameter precision (coefficient of variance [CV]), parameter difference and correlation with relative enhancement ratio (RER) and initial area under the curve (IAUC) from dynamic contrast‐enhanced (DCE) MRI of the three methods were determined and compared. Results Among the three biexponential methods, Method 1 best described most of the pixels (63.20% based on R2; 44.52% based on Akaike Information Criteria). The CV of D calculated from Method 2/3 (14.95%/13.90%), the CV of D* from Method 2 (77.04%) and the CV of f from Method 3 (80.87%) were the lowest among the three methods. Significant difference was observed for each IVIM‐derived parameter calculated from all the three methods (P = 0.000–0.005). Only the perfusion‐related f value calculated from Method 2 was correlated with RER (r = 0.548; P = 0.002) or IAUC (r = 0.561; P = 0.001). Conclusion IVIM‐derived parameters differ depending on the calculation methods. The two‐step fitting method with D value estimation first was correlated with DCE MRI perfusion. J. Magn. Reson. Imaging 2015;42:362–370.